Influences of non-uniformly distributed forming loads on deformation sequence and texture evolution in tailor heat treated Al6014 blanks - Nan Xiang; Meng-han Yang; Wan-ting Sun; Tao Huang; Hai-rui Zhang; Peng-yi Wang; Fei-yang Cheng (Journal of Materials Research and Technology)
Tailor heat treatment (THT)-induced local material softening of precipitation-hardening alloy sheet can provide a simplified process routine for the manufacture of shell components with regional complex shape. Nevertheless, the challenges are also introduced, such as excessive plastic deformation and increased risk of rupture in the softened region, leading to diminished formability of the sheet metal. In this study, to address these issues, a control strategy that utilizes non-uniformly distributed pressure (NUDP) to regulate the regional deformation behaviors of tailor heat treated blank (THTB) is proposed. The results demonstrate that utilizing heterogeneous elastomers can generate a gradient pressure field between the ''heat-treated zone (HTZ)'' and the ''as-received zone (ARZ)'' of Al6014 aluminum alloy THTB. Such NUDP can effectively reduce the normal pressure and in-plane stresses in the HTZ to postpone the onset of yielding of HTZ, and thereby the deformation sequence in these two specific regions can be controlled compatibly. Accrodingly, the limit bulge height (LBH) of THTB obtained from bulge test can be increased by 17.5%, while uniformity of strain distribution between HTZ and ARZ can be improved by 33.9%. It can be found that through the introduction of NUDP, recrystallization texture (e.g., Cube texture) generated by THT is predominately transformed into non-deformation texture (e.g., P-type texture) in the HTZ. Meanwhile, the intensity of deformation texture remains almost unchanged, which is conductive to the prevention of premature rupture in the HTZ. This activation of deformation mechanism can be favorable for the improvement of the overall forming limit and the strain distribution uniformity in THTB.